The antecedents of brand loyalty through the Attitude-Relationship approach - Rayane , Amina (Dirassat Journal Economic Issue, 2024)
The objective of this article is to identify the antecedents of customer loyalty according to the attitude-relationship approach. By trying to propose a conceptual model empirically validated on the Algerian mobile phone market, this study tried to integrate attitudinal and relational variables in order to understand loyalty not as a buying behaviour but rather as a relationship taking into account its different facets: perceptive, cognitive and conative.